Sovereignty: Some considerations - I. Duncanson (Law Text Culture, 2008)
The purpose of this paper is to assert that sovereignty is not a useful doctrine when applied domestically in modern times in the form it often assumes, namely a locus of legal or political authority which has an existence beyond the political system governed by it and which may therefore have resort to extraordinary power in exceptional circumstances. The conviction that this must be so has gained the status of common sense in some circles: after all, must the state not have emergency powers to protect itself ? But what is ‘itself ’? — a question that arises whenever ‘state’ infrastructure is sold to largely wealthy purchasers. Is the state not the taxpayers’ agent? Why should they be asked to pay over again for assets they already own?